Research of compound Nd:YAG phase-conjugate resonator with stimulated Brillouin scattering (SBS) cell - Qu, Jun; Zhang, Weijun; Gao, Xiaoming (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
How to improve the quality of output beam of phase conjugation cavity is a problem. In this paper, the output characteristic of compound phase-conjugate resonator with stimulated Brillouin scattering (SBS) cell was reported. The experimental results indicated it has high output energy and excellent stability. The output energy of the single pulse can reach 90 mJ, and the width of it is about 25 ns. The results of pulse widths, output energies and beam profiles were given.
Optica Applicata, Vol. 35, 2005, nr 1, s. 43-47
Keywords: optyka; nonlinear optical; stimulated Brillouin scattering (SBS); phase-conjugation; compound resonator